1984
DOI: 10.1177/0148607184008002146
|View full text |Cite
|
Sign up to set email alerts
|

Consultative Total Parenteral Nutrition Teams: The Effect on the Incidence of Total Parenteral Nutrition‐Related Complications

Abstract: A two part, prospective study was undertaken to establish the existing frequency of total parenteral nutrition-(TPN) related mechanical, metabolic, and septic complications in an institution with a consultative TPN team (group A) and to determine if increasing the involvement of the TPN team in patient monitoring and verifying adherence to TPN infection control guidelines would reduce the incidence of these complications (group B). The initial 28 consecutive patients were managed entirely by their primary phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
5

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 15 publications
0
63
0
5
Order By: Relevance
“…The sample sizes in the trials were generally small and ranged from 28 2 to 285, 17 subjects, with 5 studies having unequal sample sizes between the comparison groups. 3,5,6,15,17 The mean duration for the administration of TPN therapy ranged from 7.1 days 2 to 26 days 16 and was administered using either a central [3][4][5][6][12][13][14][15]17 or peripheral 4,5,12 venous catheter. In 2 studies, 2,4 patients received oral and or enteral nutrition during the transitional phase of TPN therapy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample sizes in the trials were generally small and ranged from 28 2 to 285, 17 subjects, with 5 studies having unequal sample sizes between the comparison groups. 3,5,6,15,17 The mean duration for the administration of TPN therapy ranged from 7.1 days 2 to 26 days 16 and was administered using either a central [3][4][5][6][12][13][14][15]17 or peripheral 4,5,12 venous catheter. In 2 studies, 2,4 patients received oral and or enteral nutrition during the transitional phase of TPN therapy.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5][6]12,13,15,17 None of the studies demonstrated a statistically significant difference in the incidence of potassium abnormalities in patients who were managed by the TPN team and those not managed by the TPN team.…”
Section: Potassiummentioning
confidence: 99%
“…Studies that investigated the role of a nutrition support team indicated a reduced inappropriate TPN use, less catheter-related sepsis, and even improved survival (14)(15)(16)(17)(18)(19). These outcomes were already shown in the 1980s (18,19). The improved efficacy of TPN use resulted in reduced costs in most studies (14)(15)(16).…”
Section: Discussionmentioning
confidence: 98%
“…Numerous papers have associated the establishment of an NST with improved clinical outcome and/or reduction in costS.25, 28,30,34,66,[70][71][72][73][74][75][76][77][78][79][80][81][82][83] The apparent implication of such data is that every hospital should have an NST. A difficulty with interpreting and implementing such a conclusion is the wide variability in already established NSTs, as discussed above.…”
Section: Data On the Efffects Of The Nstmentioning
confidence: 99%
“…Of the 133 medical centers that responded, 45% had already formed an NST, and another 15% were in the process of doing so. A repeat survey24 done in 1983 revealed that, by then, 80.5% (of 149 hospitals that responded) had an NST.…”
mentioning
confidence: 99%